TREND PENELITIAN KEMAMPUAN LITERASI SAINS MAHASISWA DI PERGURUAN TINGGI: SYSTEMATIC LITERATURE REVIEW - Rozi, Fahrur; Molliq Rangkuti, Yullita; Surya, Edy (Universitas Negeri Medan, 2024)
Based on data released by Central Connecticut State University in 2016 with the title World's Most Literate Nations, stating that Indonesia ranks 60th out of 61 countries in terms of literacy skills, it can be said that literacy skills in Indonesia are still very minimal. Indonesia has a